Determination of platinum group elements in terrestrial rocks using nickel sulfide fire assay isotope dilution ICP-MS = (Penentuan Unsur Kumpulan Platinum Dalam Batuan Menggunakan Pencairan Isotop ICP-MS Assay Api Nikel Sulfida) - Wee, Boon Siong; Ebihara, Mitsuru; Wood, A. K. H. (Malaysian Analytical Sciences Society (ANALIS), 2011)
Platinum group elements (PGE: Ru, Rh, Pd, Os, Ir, Pt) are highly siderophile elements (HSE) and their abundances in terrestrial rocks are low (~ ppb). This group of elements is important for understanding of geochemical processes, essential in mineral exploration, environmental studies, and identification of impact craters. Determination of PGE is very challenging and a reliable analytical technique is required to obtain high quality data. This study aims to utilize the fire assay isotope dilution inductively coupled plasma mass spectrometry (ICP-MS) for the determination of platinum group elements in terrestrial rock samples (WPR-1, WMG-1, and UMT-1). The nickel sulfide fire assay is applied to preconcentrate PGE from terrestrial rocks. All samples (about 0.2 – 0.5 g) were spiked with enriched isotopes (except Rh) prior to fire assay procedure in order to achieve isotope equilibrium. The NiS beads obtained were dissolved in HCl and the residue containing PGE was then dissolved prior to ICP-MS measurement. Isotopic ratios of PGE were measured and concentrations were calculated using the isotope dilution equation. The recoveries are in the range of 60 – 85% for all PGE except Os, which is prone not to be quantitatively collected due to the formation of OsO4 . However, the lost of analytes does not affect the accuracy of the data obtained once the equilibrium between elements in samples and spikes is established. Actually, an excellent agreement between our data and literature values was confirmed for Os data. The measurement of PGE using ICP-MS requires correction from monoatomic and polyatomic ions having the same mass-to-charge ratio as those of analytes of interest. Instrument memory effect is evident in Os measurements and flushing with HCl and TMSC were adequate to reduce the memory effect. Low sample blanks (< 12 pg/g) and detection limits (< 15 pg/g) were achieved. In conclusion, the present method is able to determine PGE with reasonable accuracy despite of small sample size and is very favorable for application to terrestrial samples.